Body electrical loss analysis (BELA) in the assessment of visceral fat: a demonstration - Blomqvist Kim H; Lundbom Jesper; Lundbom Nina; Sepponen Raimo E (BioMedical Engineering OnLine, 2011)
Abstract Background Body electrical loss analysis (BELA) is a new non-invasive way to assess visceral fat depot size through the use of electromagnetism. BELA has worked well in phantom measurements, but the technology is not yet fully validated. Methods Ten volunteers (5 men and 5 women, age: 22-60 y, BMI: 21-30 kg/m2, waist circumference: 73-108 cm) were measured with the BELA instrument and with cross-sectional magnetic resonance imaging (MRI) at the navel level, navel +5 cm and navel -5 cm. The BELA signal was compared with visceral and subcutaneous fat areas calculated from the MR images. Results The BELA signal did not correlate with subcutaneous fat area at any level, but correlated significantly with visceral fat area at the navel level and navel +5 cm. The correlation was best at level of navel +5 cm (R2 = 0.74, P < 0.005, SEE = 29.7 cm2, LOOCV = 40.1 cm2), where SEE is the standard error of the estimate and LOOCV is the root mean squared error of leave-one-out style cross-validation. The average estimate of repeatability of the BELA signal observed through the study was ±9.6 %. One of the volunteers had an exceptionally large amount of visceral fat, which was underestimated by BELA. Conclusions The correlation of the BELA signal with the visceral but not with the subcutaneous fat area as measured by MRI is promising. The lack of correlation with the subcutaneous fat suggests that subcutaneous fat has a minor influence to the BELA signal. Further research will show if it is possible to develop a reliable low-cost method for the assessment of visceral fat either using BELA only or combining it, for example, with bioelectrical impedance measurement. The combination of these measurements may help assessing visceral fat in a large scale of body composition. Before large-scale clinical testing and ROC analysis, the initial BELA instrumentation requires improvements. The accuracy of the present equipment is not sufficient for such new technology.